Politics and religion in the modern world - Moyser, George (Routledge, 1991)
Despite the commonly held Western view that secularisation has taken religion out of the political sphere, the relationship between religion and politics is at the heart of many of the critical issues of our time. The role of the church in nationalist movements in Eastern Europe, and the influence of Islam on Middle Eastern politics are two clear examples. Politics and Religion in the Modern World sets out to examine what makes religion and politics such a potent combination in countries around the world. It is an important analysis of the relationship between religion and politics, which will be recommended reading for students of political science, religious studies, and sociology.